Pengaruh Iklan, Sales Promotion, Dan Citra Merek Terhadap Minat Beli Ulang (Studi Pada Pengguna Shopee) - Azmi, Maulida (Journal of Entrepreneurship, Management and Industry (JEMI), 2022)
The purpose of this paper is to examine the impact of advertisement, sales promotion and brand image on repurchase intention. The respondents were the customers of Shopee, an online shopping platform. This study is quantitative in nature. A total of 200 questionnaires were distributed to the target respondents and 110 were returned. Various statistical analyses were employed to test the model. The result also confirmed that all the dimensions of the variables were good constructs. The finding found that the relationship between advertising, sales promotion and brand image and are significant.